Five-day resynch programs in dairy cows including controlled internal drug release at two stages post-artificial insemination - Stephanie Leeann Pulley; Scott L. Hill; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2013)
Two experiments were conducted to assess pregnancy outcomes after a 5-day Ovsynch-56 Resynch (RES; gonadotropin-releasing hormone injection 5 days before [GnRH-1; d 0] and 56 hours (GnRH-2) after PGF2α[PG] injections on day 5 and 6, timed artificial insemination [TAI] on day 8) with and without a progesterone-releasing intravaginal controlled internal drug release (CIDR) 5-day insert. In Exp. 1, nonpregnant cows were enrolled on day 34 post- AI: day 34 RES-CON (n = 528) or day 34 RES-CIDR (n = 503). Blood was collected for progesterone assay. Pregnancy per AI (P/AI) was diagnosed by uterine palpation per rectum at 34 and 62 days post-TAI. Only 76% of 1,031 cows had high progesterone (≥1 ng/mL) on day 34 at the nonpregnant diagnosis. No differences in P/AI were detected between treatments. The day-34 RES-CIDR cows with low (/mL) progesterone, however, had greater (P = 0.036) P/AI than day-34 RES-CON cows (37.7 vs. 29.4%), whereas day-34 RES-CIDR cows with high progesterone had lesser P/AI than day-34 RES-CON (27.4 vs. 34.3%). In Exp. 2, cows were enrolled on day 31 post-AI after a nonpregnant diagnosis: (1) day 31 PG-3-G (n = 102): Pre-PG on day 31, Pre-GnRH on day 34, and RES on day 41 (n = 102); (2) day 41 RES-CON (n = 108) as Exp. 1, but on day 41; and (3) day 41 RES-CIDR (n = 101) as Exp. 2, but on day 41. Blood was collected for progesterone assay and ovarian structures were mapped by ultrasonography on days 31, 34, 41, 46, and 48. Pregnancy was diagnosed by ultrasonography on days 31 and 59 post-TAI. The proportion of cows with high progesterone on day 31 was 70.6%. More (P<0.001) cows ovulated after Pre-GnRH on day 31 PG-3-G (60.4%) than for day 41 RES-CON (12.5%) or day 41 RES-CIDR (17.1%). More (P<0.001) PG-3-G cows had luteolysis after Pre-PG on day 31 than other treatments (73.7 vs.<11%). The proportion of cows with high progesterone on day 41 at GnRH-1 tended (P = 0.10) to be greater for PG-3-G (75.6%) than for other treatments (65 to 70%). The P/AI was greater in cows starting RES on day 41 when progesterone was low (44%) than when it was high (33%), but no treatment differences were detected 31 days after TAI (PG-3-G = 33.3%; d 41 RES-CON = 38.9%; d 41 RES-CIDR = 35.6%). We concluded that improved P/AI for cows initiating the 5-day RES on day 34 without a corpus luteum is progesterone-dependent because addition of the CIDR insert to the RES treatment improved P/AI in cows with low progesterone (Exp. 1). Although day-31 PG-3-G increased luteolysis and produced greater ovulation rates before the onset of RES, no increase in P/AI was detected compared with RES started on day 41 with or without a CIDR insert.; Dairy Day, 2013, Kansas State University, Manhattan, KS, 2013; Dairy Research, 2013 is known as Dairy Day, 2013
Keywords: Dairy Day; 2013; Kansas Agricultural Experiment Station contribution; no. 14-179-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 1093; CIDR; Resynch; Pregnancy